Millennial slip rate of the Longitudinal Valley fault from river terraces : implications for convergence across the active suture of eastern Taiwan - Shyu, J. Bruce H. (2012)
The Longitudinal Valley fault is a key element in the active tectonics of Taiwan. It is the principal structure accommodating convergence across one of the two active sutures of the Taiwan orogeny. To understand more precisely its role in the suturing process, we analyzed fluvial terraces along the Hsiukuluan River, which cuts across the Coastal Range in eastern Taiwan in the fault's hanging wall block. This allowed us to determine both its subsurface geometry and its long-term slip rate. The uplift pattern of the terraces is consistent with a fault-bend fold model. Our analysis yields a listric geometry, with dips decreasing downdip from about 50° to about 30° in the shallowest 2.5 km. The Holocene rate of dip slip of the fault is about 22.7 mm/yr. This rate is less than the 40 mm/yr rate of shortening across the Longitudinal Valley derived from GPS measurements. The discrepancy may reflect an actual difference in millennial and decadal rates of convergence. An alternative explanation is that the discrepancy is accommodated by a combination of slip on the Central Range fault and subsidence of the Longitudinal Valley floor. The shallow, listric geometry of the Longitudinal Valley fault at the Hsiukuluan River valley differs markedly from the deep listric geometry illuminated by earthquake hypocenters near Chihshang, 45 km to the south. We hypothesize that this fundamental along-strike difference in geometry of the fault is a manifestation of the northward maturation of the suturing of the Luzon volcanic arc to the Central Range continental sliver.